Uji Efektivitas Antibakteri Ekstrak dan Fraksi Bunga Telang (Clitoria Ternatea L.) terhadap Pertumbuhan Staphylococcus Aureus ATCC 25923: Penelitian - Tantri Dwi Lestari; Tatiana Siska Wardani; Vivin Marwiyati Rohmana (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Acne is a skin disease where the oil glands are blocked by dirt that can be infected by bacteria. One way to cure acne is by using compounds that have antibacterial effects. Butterfly pea flowers contain compounds that are believed to inhibit bacterial growth at a certain percentage. The purpose of this study was to determine the antibacterial effectiveness of butterfly pea flower extracts and fractions in certain concentrations. This type of research uses experimental. This study was divided into 6 groups with 4 different concentrations, namely positive control (Gentamicin), negative control (DMSO 10%), Butterfly pea flower extract (15%, 20%, 30%, 40%), Aquadest Fraction (15%, 20%, 30%, 40%), N-hexane Fraction (15%, 20%, 30%, 40%), and Ethyl acetate fraction (15%, 20%, 30%, 40%). The results of the bacterial inhibition zone data were analyzed using SPSS 26 with a confidence level of 95%. The results of this study indicate that the extract and fraction of butterfly pea flowers provide antibacterial effects on the growth of staphylococcus aureus bacteria at concentrations of 15%, 20%, 30%, and 40%. The best inhibition zone is in the ethanol extract of butterfly pea flowers with an average inhibition zone of 9.3 mm at a concentration of 40%.